The first troglophilic terrestrial isopods (Isopoda: Oniscidea) from Iran with a description of a new species - Ghasem Mohammadi Kashani; M. Dashan; S. Sadeghi (Iranian Journal of Animal Biosystematics, 2016)
The present study reports on the first troglophilic terrestrial isopod from Iran. Protracheoniscus faramarzi n. sp. was found in Shafagh Cave, southern Iran. The new species is described and its diagnostic characters are figured. This species is distinguished by the long and narrow antennae, the reduced body pigmentation and the number of ommatidia